A 'deep' aesthetics of contested landscapes: Visions of land use as competing temporalities. Issue 95 (October 2018) - Jenkins, Jeffrey
Abstract: Multiple use forests in the United States take on different meanings for people who live, work, and recreate on the land. Forests are imbued with often contested visions of what the landscape is and ought to be, and this is related to the various knowledges, values, and experiences of users who project social, political, and economic power. The resources and amenities of multiple use public lands in the American West are typically managed as common property for sustained-yield and equal access. The major exception to this being the priority given to hardrock mining, which is legally designated as the "highest and best use". This article looks at a proposed rare earth mine in the Black Hills of Wyoming to assess how aesthetic representations and meanings of the forest are situated in the politics of resource access and control. While previous work has looked at the role of contested aesthetics within the same spatial extent, this article proposes a deeper aesthetic that takes time and the weight of history into account. Four discourse coalitions are analyzed: Native American ontological constructs of land as spatiotemporally divergent from dominant frontier sectionalism, competing epistemologies of positivist science and land-based livelihoods, perceptions of risk and geopolitical control extended to the subsurface, and the rationalization of scenic amenities and recreational access. The paper seeks to unravel different power connections to explain the emergence of land use conflict through a temporal disentanglement of the knowledge structures that have produced aesthetic meaning.